Rivaroxaban in atrial fibrillation cardioversion: an update - Lavalle C; Straito M; Caroli A; Piro A; Giunta G; Mariani MV; Fedele F (Dove Medical Press, 2019)
Carlo Lavalle, Martina Straito, Annalisa Caroli, Agostino Piro, Giuseppe Giunta, Marco Valerio Mariani, Francesco FedeleDepartment of Cardiovascular, Respiratory, Nephrological, Anesthesiological and Geriatric Sciences, “Sapienza” University of Rome, Policlinico Umberto I, Rome, ItalyAbstract: Currently, atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, with a prevalence of about 2–3% in the general population, representing a powerful risk factor for stroke and systemic thromboembolism and increased mortality and morbidity. Restoration of sinus rhythm is an important treatment option in AF and has a high success rate, but there is the need for an effective anticoagulation strategy to reduce the risk of embolic events. Anticoagulation with vitamin K antagonists is often associated with failure to achieving effective international normalized ratio. In this setting, recent data have led to extended approval for rivaroxaban in clinical practice, because it is effective and safe in patients with AF undergoing cardioversion, avoiding additional health costs and related time loss, while improving patient satisfaction. The present report provides an overview of the main randomized controlled trial and the main real-life studies, documenting the use of rivaroxaban in patients with non-valvular AF who underwent the cardioversion procedure. Considering that novel non-vitamin K antagonist oral anticoagulants in left atrial appendage thrombi resolution is still unknown in the real-world practice, the main findings on the use of rivaroxaban in this setting are also discussed.Keywords: atrial fibrillation, cardioversion, novel oral anticoagulants, rivaroxaban, thrombus